About evaluation of nutritive state in premature infants - K. V. Dashichev; N. V. Olendar; T. G. Pukhova; E. P. Sitnikova (LLC "Diagnostics and Vaccines", 2021)
Insulin-like growth factor 1 (IGF-1) plays an important role in the energy balance of the newborn baby's body, is associated with protein stores, which allows us to consider its level as an indicator of nutritional status.Objective: to study the value of insulin-like growth factor 1 and basic nutrients in the blood in premature infants in the process of neonatal adaptation.Materials and methods. Dynamics blood levels of insulin-like growth factor 1 in premature newborns included two trends: decrease (1 group) and increase (2 group). During a pregnancy most mothers of newborns from 1 group had been nonspecific respiratory and urinary-sexual organs'sinfectious diseases, in mothers of newborns from 2 group prevailed disorders which carried high risk of fetal hypoxia. During a neonatal period blood levels of albumen of newborns from 1 group decreased and blood levels of glucose increased; blood levels of nutrients in newborns from 2 group did not change.Conclusions. Dynamics blood levels of insulin-like growth factor 1 in premature newborns are markers of metabolism's processes which were originated in fetal stage and continue in the neonatal period.